1988
DOI: 10.1128/iai.56.5.1320-1325.1988
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of chlamydial genital infection in B-cell-deficient mice and immunity to reinfection

Abstract: The purpose of this investigation was to determine the relative roles of the humoral and cell-mediated immune responses in the resolution of chlamydial genital infection of mice and resistance to reinfection. To this end, female BALB/c mice were rendered B cell deficient by treatment with heterologous anti-immunoglobulin M (IgM) serum from birth. Controls were similarly treated with either normal serum or phosphate-buffered saline. Before inclusion in each experiment, aiti-IgM-treated mice were screened for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 26 publications
6
130
2
Order By: Relevance
“…This ®nding is in agreement with previous studies demonstrating that local antibodies play a subordinate role also in short-term anti-chlamydial protection. 11,14,15 Somewhat at variance with the present study, Su et al reported that mMT mice were more susceptible to reinfection than were WT mice, at 70 days following a primary infection. Of note, we observed that clearing of the transient local infection was delayed in some of the memory mMT mice, but not in the WT mice, which may indicate that antibodies can in¯uence the course of the transient infection.…”
Section: Discussioncontrasting
confidence: 60%
“…This ®nding is in agreement with previous studies demonstrating that local antibodies play a subordinate role also in short-term anti-chlamydial protection. 11,14,15 Somewhat at variance with the present study, Su et al reported that mMT mice were more susceptible to reinfection than were WT mice, at 70 days following a primary infection. Of note, we observed that clearing of the transient local infection was delayed in some of the memory mMT mice, but not in the WT mice, which may indicate that antibodies can in¯uence the course of the transient infection.…”
Section: Discussioncontrasting
confidence: 60%
“…After the challenge, mice were observed twice daily for clinical signs of adverse reaction to infection. To assess the level of infection, cervicovaginal swabs were collected from each animal every 3 days following the challenge and C. muridarum was isolated from swabs in tissue culture by standard methods (Ramsey et al, 1988). The experiment was repeated to contain 12-15 mice per group.…”
Section: Intravaginal Challenge By Live Chlamydiamentioning
confidence: 99%
“…Chlamydia muridarum was used as purified infectious elementary bodies (Ramsey et al, 1988) or inactivated by UV irradiation as previously described (Caldwell et al, 1981).…”
Section: Chlamydiae Antibodies and Diabodiesmentioning
confidence: 99%